Enriching the international tourist experience of local Malaysian cuisine and a guarantee of a purchase intention - Saad, Mazni; AbdulRahman, Nadhirah; Umadi, Muhammad Fikri (Association of Malaysian Environment-Behaviour Researchers (AMER), 2019)
Gastronomy tourism contributes to about one-fifth of the Malaysian economy, indicating that people travel to the country are probably interested in experiencing the taste of the food. This study aims to identify the tourists’ experience as well as their purchase intention of local Malaysian food. The findings of 202 international tourists at Bukit Bintang in Kuala Lumpur highlighted both the characteristics of local Malaysian food and environmental factors as significant influences in the tourists’ willingness to purchase and to savour local food again. Their potential return visit to the country will benefit the tourism industry and the country’s foreign exchange